Long-term results of Nd:YAG laser destruction of epithelial ingrowth after Femto-LASIK and ReLEx Smile - I.V. Dutchin; M.V. Pshenichnov (Офтальмохирургия)
Purpose. To evaluate long term cornea characteristics after Nd:YAG laser destruction of epithelial ingrowth in patients after Femto-LASIK and ReLEx Smile and assess its safety according to the state of the corneal endothelium. Material and methods. Due to the rather rare development of this condition, clinical material is presented by 6 cases (6 eyes): 4 men and 2 women aged 22 to 43 years, average 34.6±2.7 years. The average degree of myopia is –4.75 diopters. The Femto-LASIK technique was performed in 3 eyes, and ReLEx Smile – in 3 eyes. All surgeries were carried out without complications, the patients were discharged at the place of residence with the usual recommendations. The timing of epithelial ingrowth after refractive surgery varied from one week to 3 months. The number of sessions of Nd:YAG laser destruction varied regardless of the type of epithelial ingrowth and the technique of previous refractive surgery. The safety of the treatment was confirmed by studying the state of the corneal endothelium of the operated patients. Results. In all 6 cases, it was possible to achieve complete destruction of the zones of epithelial ingrown. Epithelial ingrowth was eliminated at one patient in 5 sessions, at two – in 3 sessions, at two – in 2 sessions and at one – in one session. The number of sessions and the number of impulses in different patients varied greatly and it was not possible to draw a direct parallel between the volume of epithelial ingrown and the total number of impulses. Conclusion. Analysis of long-term results of treatment of epithelial ingrowth by the method of Nd:YAG laser destruction showed good efficiency and atraumaticity for the cornea. The advantage of this technique is its ease of implementation, which is especially important after the ReLEx Smile technology. The use of Nd:YAG laser is effective method of epithelial ingrowth destruction.